Social safety nets in Nepal: A review - Adhikari, Madan; Kishore, Avinash; Koirala, Pankaj; Rashid, Shahidur; Isha Chand (CSISA, 2024)
Governments across the world have established social protection systems where they implement programs to eradicate extreme poverty, address rising inequality, foster inclusive growth, and provide crucial assistance to the most vulnerable segments of society. These programs involve in-kind or cash transfers through a system (World Bank, 2012), or public employment at guaranteed wages (Rahman and Pingali, 2024). Additionally, social protection programs provide poor communities, households, and individuals support to increase their resilience to economic risks and catastrophic events. Social protection programs can be classified into three broad categories based on their objectives and the risks they cover: • Social security programs include contributory programs that offer workers in formal and informal sectors of the economy and their dependents pensions, gratuities, health insurance and related support during employment and after retirement.• Labor market programs focus on individuals’ skill building in the job market through vocational training programs, connecting them to potential employers through employment service centers and employment management information systems, and providing financial and logistical support for foreign employment.  • Non-contributory social assistance programs, or social safety net (hereafter, SSN) programs, often (but not always) support for poor and vulnerable individuals, households, and communities. These programs are in various forms including cash transfers or vouchers, in-kind transfers, school feeding and other targeted food assistance programs, labor-intensive public work programs, scholarships, and humanitarian and disaster relief programs.